2018
DOI: 10.1088/1361-6560/aae8a9
|View full text |Cite
|
Sign up to set email alerts
|

Auto-delineation of oropharyngeal clinical target volumes using 3D convolutional neural networks

Abstract: Accurate clinical target volume (CTV) delineation is essential to ensure proper tumor coverage in radiation therapy. This is a particularly difficult task for head-and-neck cancer patients where detailed knowledge of the pathways of microscopic tumor spread is necessary. This paper proposes a solution to auto-segment these volumes in oropharyngeal cancer patients using a two-channel 3D U-Net architecture. The first channel feeds the network with the patient's CT image providing anatomical context, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…For example, using the combination of a deep learning neural network and a shape representation model, Tong et al recently published a competitive algorithm that can delineate 9 OARs on a new scan under 10 seconds (20). Similarly, Cardenas et al (21,22)have shown that rapid CTV generation can be performed with machine learning approaches, obviating an often time-consuming step in target delineation. Although these results are promising, general consensus remains that automatic segmentation has yet to completely replace physician contouring, as manual checks and sometimes adjustments remain necessary(23); Voet et al (24), for example, showed that a commercial-softwareautosegmented CTV protocol delivered clinically meaningful undercoverage, which was not reflected decisively in similarity metric assessment, despite potential clinical risk if implemented without oversight.…”
Section: Modern Artmentioning
confidence: 99%
“…For example, using the combination of a deep learning neural network and a shape representation model, Tong et al recently published a competitive algorithm that can delineate 9 OARs on a new scan under 10 seconds (20). Similarly, Cardenas et al (21,22)have shown that rapid CTV generation can be performed with machine learning approaches, obviating an often time-consuming step in target delineation. Although these results are promising, general consensus remains that automatic segmentation has yet to completely replace physician contouring, as manual checks and sometimes adjustments remain necessary(23); Voet et al (24), for example, showed that a commercial-softwareautosegmented CTV protocol delivered clinically meaningful undercoverage, which was not reflected decisively in similarity metric assessment, despite potential clinical risk if implemented without oversight.…”
Section: Modern Artmentioning
confidence: 99%
“…The CNN algorithm was chosen to develop an autocontouring tool because other studies have shown that CNN‐based models outperform most other machine learning‐based and model‐based algorithms in contouring head and neck structures. Zhu et al, showed that their CNN‐based autocontouring algorithm for head and neck normal structures could achieve the equivalent performance with the best MICCAI 2015 challenge results with the atlas‐ and model‐based algorithms .…”
Section: Introductionmentioning
confidence: 99%
“…Comparison setup and metrics: We use 3-fold cross-validation, separated at the patient level, to evaluate performance of our approach and the competitor methods. We compare against setups using only the CT appearance information [14,15] and setups using the CT with binary GTV/LN masks [3]. Finally, we also compare against setups using the CT + GTV/LN SDMs, which does not consider the OARs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…1, CTV delineation depends on the radiation oncologist's visual judgment of both the appearance and the spatial configuration of the GTV, LNs, and OARs, suggesting that only considering the RTCT makes the problem ill-posed. Supporting this, Cardenas et al recently showed that considering the GTV and LN binary masks together with the RTCT can boost oropharyngeal CTV delineation performance [3]. However, the OARs were not considered in their work.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation